PRARANCANGAN PABRIK BUTIL METAKRILAT DARI ASAM METAKRILAT DAN BUTANOL DENGAN KAPASITAS 80.000 TON/ TAHUN - , JOANNA RUTH KARLIENA; , Dr. Edia rahayuningsih, M.S. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Butyl methacrylate is an ester compound that is widely used in industries such as leather coating, polishing floor, coating, adhesive and paint as a pigment dispersant and adhesion promoter. Development opportunities of butyl metharcylate industry in Indonesia is quite large, considering that there is no manufacturer listed has been established in Indonesia. The plant is planned to operate for 330 days / year with a butyl methacrylate production capacity of 80000 tons / year. The main raw material required is as much as 42399,1656 ton / year of butanol and 48205,9512 tons / year of methacrylic acid. The method used is the esterification with Styrene divinylbenzene co-polymer beads catalyst. In general, butyl methacrylate manufacturing stages process is as follows: (i) reaction between butanol and methacrylic acid with solid catalyst in a fixed bed reactor, (ii) separation of organic and water phase by using the density of the liquid, (iii) butyl methacrylate product purification through distillation. As a support, utility plant unit supplies the cooling water as much as 28,43 tons / hour, 390,19 kVA electricity, compressed air up to 100 m3/hr, and 0,51 tons / hoursteam. The plant will be established in the city of Cilegon, West Java province, with consideration of raw material oriented. Cilegon region close to the butanol industry, and close to the harbor making it easier to procure raw materials methacrylic acid imported from China as well as the marketing of the product butyl methacrylate. Plant location close to the river, so that the source of water for utility plant unit derived from river water. Calculation of economic evaluation results is fixed capital required equal to $132,130,815,97 and working capital equal to $66,535,078.17. At 100% production rate, obtained ROI before tax of 53,76 %, ROI after tax of 26,88 %, POT before tax of 1,57 years, POT after tax of 2,71 years, with BEP at 42,11 %, SDP at 13,98 %, and 29,69 % for DCFRR. Based on consideration of the economic evaluation results, this butyl methacrylate plant with capacity 80000 tons / year worth to be studied further.